Pathophysiology of bone disease in chronic kidney disease: from basics to renal osteodystrophy and osteoporosis - Aguilar, Armando; Gifre, Laia; Ureña-Torres, Pablo; Carrillo-López, Natalia; Rodriguez-García, Minerva; Massó, Elisabeth; da Silva, Iara; López-Báez, Víctor; Sánchez-Bayá, Maya; Prior-Español, Águeda; Urrutia, Marina; Paul, Javier; et al. (Frontiers in Physiology, 2023)
Chronic kidney disease (CKD) is a highly prevalent disease that has become a public health problem. Progression of CKD is associated with serious complications, including the systemic CKD-mineral and bone disorder (CKD-MBD). Laboratory, bone and vascular abnormalities define this condition, and all have been independently related to cardiovascular disease and high mortality rates. The “old” cross-talk between kidney and bone (classically known as “renal osteodystrophies”) has been recently expanded to the cardiovascular system, emphasizing the importance of the bone component of CKD-MBD. Moreover, a recently recognized higher susceptibility of patients with CKD to falls and bone fractures led to important paradigm changes in the new CKD-MBD guidelines. Evaluation of bone mineral density and the diagnosis of “osteoporosis” emerges in nephrology as a new possibility “if results will impact clinical decisions”. Obviously, it is still reasonable to perform a bone biopsy if knowledge of the type of renal osteodystrophy will be clinically useful (low versus high turnover-bone disease). However, it is now considered that the inability to perform a bone biopsy may not justify withholding antiresorptive therapies to patients with high risk of fracture. This view adds to the effects of parathyroid hormone in CKD patients and the classical treatment of secondary hyperparathyroidism. The availability of new antiosteoporotic treatments bring the opportunity to come back to the basics, and the knowledge of new pathophysiological pathways [OPG/RANKL (LGR4); Wnt-ß-catenin pathway], also affected in CKD, offers great opportunities to further unravel the complex physiopathology of CKD-MBD and to improve outcomes.